Microscopic Traffic Simulation outputs for "Evaluation of the potential of speed-limiting geofencing" : Data set for VTI rapport 1190A - Olstam, Johan; Bhattacharyya, Kinjal; Gebrehiwot, Rihanna (Swedish National Road and Transport Research Institute, 2024)
This data repository contains all outputs from the microscopic traffic simulation experiment of speed-limiting geofencing for a hospital zone in an urban corridor of Gothenburg, Sweden as a part of the research project entitled "Evaluation of the potential of speed-limiting geofencing" (VTI rapport 1190A). The outputs include speed distributions, 85th Percentile speeds, tailpipe emissions and energy use for interrupted (signalized pedestrian crossing) and uninterrupted road facility and for different market penetration rates of geofenced vehicles at different demand levels.

The dataset was originally published in DiVA and moved to SND in 2024.

This data repository contains all outputs from the microscopic traffic simulation experiment of speed-limiting geofencing for a hospital zone in an urban corridor of Gothenburg, Sweden as a part of the research project entitled "Evaluation of the potential of speed-limiting geofencing" (VTI rapport 1190A). The outputs include speed distributions, 85th Percentile speeds, tailpipe emissions and energy use for interrupted (signalized pedestrian crossing) and uninterrupted road facility and for different market penetration rates of geofenced vehicles at different demand levels.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Microscopic Traffic Simulation outputs for "Evaluation of the potential of speed-limiting geofencing" : Data set for VTI rapport 1190A
Keywords: traffic safety; trafiksäkerhet; traffic areas; trafikområden; driving speed; körhastighet; simulation; simulering; Transport Systems and Logistics; Transportteknik och logistik